First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Employing optical lightning data to identify lightning flashes associated to terrestrial gamma-ray flashes - Christoph Köhn; Matthias Heumesser; Olivier Chanrion; Victor Reglero; Nikolai Østgaard; H. J. Christian; T. J. Lang; R. J. Blakeslee; Torsten Neubert (Bulletin of Atmospheric Science and Technology, 2024)
Terrestrial gamma-ray flashes (TGFs) are bursts of energetic X- and gamma-rays emitted from thunderstorms. The Atmosphere-Space Interactions Monitor (ASIM) mounted onto the International Space Station (ISS) is dedicated to measure TGFs and optical signatures of lightning; ISS LIS (Lightning Imaging Sensor) detects lightning flashes allowing for simultaneous measurements with ASIM. Whilst ASIM measures $$\sim $$ ∼ 300-400 TGFs per year, ISS LIS detects $$\sim 10^6$$ ∼ 10 6 annual lightning flashes giving a disproportion of four orders of magnitude. Based on the temporal evolution of lightning flashes and the spatial pattern of the constituing events, we present an algorithm to reduce the number of space-detected flashes potentially associated with TGFs by $$\sim $$ ∼ 60% and of associated LIS groups by $$\sim $$ ∼ 95%. We use ASIM measurements to confirm that the resulting flashes are indeed those associated with TGFs detected at approx. 400 km altitude and thus benchmark our algorithm preserving 70–80% of TGFs from concurrent ASIM-LIS measurements. We compare how the radiance, footprint size and the global distribution of lightning flashes of the reduced set relates to the average of all measured lightning flashes and do not observe any significant difference. Finally, we present a parameter study of our algorithm and discuss which parameters can be tweaked to maximize the reduction efficiency whilst keeping flashes associated to TGFs. In the future, this algorithm will hence be capable of facilitating the search for TGFs in a reduced set of lightning flashes measured from space.

Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

Inflammation and vascular remodeling in COVID-19 hearts - Christopher Werlein; Maximilian Ackermann; Helge Stark; Harshit R. Shah; Alexandar Tzankov; Jasmin Dinonne Haslbauer; Saskia von Stillfried; Roman David Bülow; Ali El-Armouche; Stephan Kuenzel; Jan Lukas Robertus; Marius Reichardt; et al. (Angiogenesis, 2023)
A wide range of cardiac symptoms have been observed in COVID-19 patients, often significantly influencing the clinical outcome. While the pathophysiology of pulmonary COVID-19 manifestation has been substantially unraveled, the underlying pathomechanisms of cardiac involvement in COVID-19 are largely unknown. In this multicentre study, we performed a comprehensive analysis of heart samples from 24 autopsies with confirmed SARS-CoV-2 infection and compared them to samples of age-matched Influenza H1N1 A ( n = 16), lymphocytic non-influenza myocarditis cases ( n = 8), and non-inflamed heart tissue ( n = 9). We employed conventional histopathology, multiplexed immunohistochemistry (MPX), microvascular corrosion casting, scanning electron microscopy, X-ray phase-contrast tomography using synchrotron radiation, and direct multiplexed measurements of gene expression, to assess morphological and molecular changes holistically. Based on histopathology, none of the COVID-19 samples fulfilled the established diagnostic criteria of viral myocarditis. However, quantification via MPX showed a significant increase in perivascular CD11b/TIE2 + —macrophages in COVID-19 over time, which was not observed in influenza or non-SARS-CoV-2 viral myocarditis patients. Ultrastructurally, a significant increase in intussusceptive angiogenesis as well as multifocal thrombi, inapparent in conventional morphological analysis, could be demonstrated. In line with this, on a molecular level, COVID-19 hearts displayed a distinct expression pattern of genes primarily coding for factors involved in angiogenesis and epithelial-mesenchymal transition (EMT), changes not seen in any of the other patient groups. We conclude that cardiac involvement in COVID-19 is an angiocentric macrophage-driven inflammatory process, distinct from classical anti-viral inflammatory responses, and substantially underappreciated by conventional histopathologic analysis. For the first time, we have observed intussusceptive angiogenesis in cardiac tissue, which we previously identified as the linchpin of vascular remodeling in COVID-19 pneumonia, as a pathognomic sign in affected hearts. Moreover, we identified CD11b + /TIE2 + macrophages as the drivers of intussusceptive angiogenesis and set forward a putative model for the molecular regulation of vascular alterations.

Localized Native American impacts on past forest composition across a regional extent in north‐eastern United States - Stephen J. Tulowiecki; Emma R. Ranney; Emily M. Keenan; Gabrielle M. Neubert; Marcie L. Hogan (Journal of Biogeography, 2022)
Aim Researchers have debated impacts of past Native American land use on forests including upon tree species composition in north‐eastern United States (US), with estimates of impacts ranging from local to regional extent. This study examines tree relative abundances to assess whether Native Americans influenced geographic distributions prior to Euro‐American settlement. Location North‐eastern United States (approx. 420,000 km 2 ). Taxon Ash ( Fraxinus spp.), basswood ( Tilia americana ), beech ( Fagus grandifolia ), birch ( Betula spp.), cherry ( Prunus spp.), chestnut ( Castanea dentata ), dogwood ( Cornus spp.), elm ( Ulmus spp.), fir ( Abies balsamea ), hemlock ( Tsuga canadensis ), hickory ( Carya spp.), ironwood ( Carpinus caroliniana and Ostrya virginiana ), maple ( Acer spp.), oak ( Quercus spp.), pine ( Pinus spp.), spruce ( Picea spp.), tamarack ( Larix laricina ) and walnut ( Juglans spp.), Methods We used boosted regression trees to model abundance patterns and to assess the importance of distance‐based proxies of Native American land use versus environmental variables. We trained models that included and excluded distance‐based proxies. Abundance estimates from original land survey records (1650–1850 CE) were acquired for taxa at 8 km spatial resolution, and related to Native American settlement locations (1500–1800 CE) and 27 environmental variables. Results When evaluated upon test data, regional‐scale models of relative abundance that included distance‐based proxies performed only slightly better than models that excluded them, with mean improvements in RMSE of 0.1 percentage points. Models suggest that Native American land use modestly altered the relative abundance of taxa locally, extending no more than 50 km from settlement. Models also suggest slight increases near settlement of a few percentage points in relative abundance for fire‐tolerant and/or dietary taxa (e.g. oak, hickory and pine), and for early‐successional taxa (e.g. ash). Main conclusions Past Native American land use had no detectable effect on forest composition across a regional extent, but increased the abundance of fire‐tolerant, shade‐intolerant and nut‐producing trees locally.

Seasonal environmental variability drives microdiversity within a coastal Synechococcus population - Kristen R. Hunter‐Cevera; Bryan R. Hamilton; Michael G. Neubert; Heidi M. Sosik (Environmental Microbiology, 2021)
Summary Marine microbes often show a high degree of physiological or ecological diversity below the species level. This microdiversity raises questions about the processes that drive diversification and permit coexistence of diverse yet closely related marine microbes, especially given the theoretical efficiency of competitive exclusion. Here, we provide insight with an 8‐year time series of diversity within Synechococcus , a widespread and important marine picophytoplankter. The population of Synechococcus on the Northeast U.S. Shelf is comprised of six main types, each of which displays a distinct and consistent seasonal pattern. With compositional data analysis, we show that these patterns can be reproduced with a simple model that couples differential responses to temperature and light with the seasonal cycle of the physical environment. These observations support the hypothesis that temporal variability in environmental factors can maintain microdiversity in marine microbial populations. We also identify how seasonal diversity patterns directly determine overarching Synechococcus population abundance features.

Seasons of Syn - Kristen R. Hunter‐Cevera; Michael G. Neubert; Robert J. Olson; Alexi Shalapyonok; Andrew R. Solow; Heidi M. Sosik (Limnology and Oceanography, 2020)
Synechococcus is a widespread and important marine primary producer. Time series provide critical information for identifying and understanding the factors that determine abundance patterns. Here, we present the results of analysis of a 16‐yr hourly time series of Synechococcus at the Martha's Vineyard Coastal Observatory, obtained with an automated, in situ flow cytometer. We focus on understanding seasonal abundance patterns by examining relationships between cell division rate, loss rate, cellular properties (e.g., cell volume, phycoerythrin fluorescence), and environmental variables (e.g., temperature, light). We find that the drivers of cell division vary with season; cells are temperature‐limited in winter and spring, but light‐limited in the fall. Losses to the population also vary with season. Our results lead to testable hypotheses about Synechococcus ecophysiology and a working framework for understanding the seasonal controls of Synechococcus cell abundance in a temperate coastal system.

Marine reserves and optimal dynamic harvesting when fishing damages habitat - Michael R. Kelly; Michael G. Neubert; Suzanne Lenhart (Theoretical Ecology, 2019)

The extreme capsule fiber complex in humans and macaque monkeys: a comparative diffusion MRI tractography study - Rogier B. Mars; Sean Foxley; Lennart Verhagen; Saad Jbabdi; Jérôme Sallet; MaryAnn P. Noonan; Franz-Xaver Neubert; Jesper L. Andersson; Paula L. Croxson; Robin I. M. Dunbar; Alexandre A. Khrapitchev; Nicola R. Sibson; et al. (Brain Structure and Function, 2016)

A Novel Approach for In Vitro Studies Applying Electrical Fields to Cell Cultures by Transformer-Like Coupling - R. Hess; H. Neubert; A. Seifert; S. Bierbaum; D. A. Hart; D. Scharnweber (Cell Biochemistry and Biophysics, 2012)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Detecting reactivity - Michael G. Neubert; Hal Caswell; Andrew R. Solow (Ecology, 2009)
By definition, ecological systems at a stable equilibrium eventually return to the equilibrium point following a small perturbation. In the short term, however, perturbations can grow. Equilibria that exhibit transient growth following perturbation are said to be reactive. In this report, we present a statistical method for detecting reactivity from multivariate time series. The test is simple and computationally tractable, and it can be applied to short time series. Its main limitation is that it is based on a model of population dynamics that is linear on a logarithmic scale. Our results suggest that the test is robust when the dynamics are nonlinear on the log scale but that it may incorrectly classify an equilibrium as reactive when the reactivity is close to zero.

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria - Thomas Müller; H.-J. Bätza; A. Beckert; C. Bunzenthal; J. H. Cox; C. M. Freuling; A. R. Fooks; J. Frost; L. Geue; A. Hoeflechner; D. Marston; A. Neubert; et al. (Archives of Virology, 2009)

Penetration Profile of Taurine in the Human Skin and Its Distribution in Skin Layers - D. L. P. da Silva; S. B. Thiago; F. A. Pessôa; Y. Mrestani; H. H. Rüttinger; J. Wohlrab; R. H. H. Neubert (Pharmaceutical Research, 2008)

Fatty acid interdigitation in stratum corneum model membranes: a neutron diffraction study - A. Ruettinger; M. A. Kiselev; Th. Hauss; S. Dante; A. M. Balagurov; R. H. H. Neubert (European Biophysics Journal, 2008)

Recent Results from Studies of Electric Discharges in the Mesosphere - T. Neubert; M. Rycroft; T. Farges; E. Blanc; O. Chanrion; E. Arnone; A. Odzimek; N. Arnold; C.-F. Enell; E. Turunen; T. Bösinger; Á. Mika; et al. (Surveys in Geophysics, 2008)

Ectomycorrhiza communities of red oak (Quercus rubra L.) of different age in the Lusatian lignite mining district, East Germany - S. Gebhardt; K. Neubert; J. Wöllecke; B. Münzenberger; R. F. Hüttl (Mycorrhiza, 2007)

What can we learn about the lipid vesicle structure from the small-angle neutron scattering experiment? - M. A. Kiselev; E. V. Zemlyanaya; V. K. Aswal; R. H. H. Neubert (European Biophysics Journal, 2006)

New insights into the structure and hydration of a stratum corneum lipid model membrane by neutron diffraction - M. A. Kiselev; N. Y. Ryabova; A. M. Balagurov; S. Dante; T. Hauss; J. Zbytovska; S. Wartewig; R. H. H. Neubert (European Biophysics Journal, 2005)

Growth rates of coastal phytoplankton from time‐series measurements with a submersible flow cytometer - Heidi M. Sosik; Robert J. Olson; Michael G. Neubert; Alexi Shalapyonok; Andrew R. Solow (Limnology and Oceanography, 2003)
Our understanding of the dynamics of phytoplankton communities has been limited by the space and timescales associated with traditional monitoring approaches. To overcome some of these limitations, we have developed a submersible flow cytometer (FlowCytobot) that is designed for extended autonomous monitoring of phytoplankton abundance, cell size, and pigmentation. FlowCytobot was moored on the seafloor from late July to October 2001 at the Long‐term Environmental Observatory study site off the coast of New Jersey, and water samples from 5 m depth were pumped continuously through the instrument. Analysis of cells' optical properties revealed distinct populations of Synechococcus and cryptophytes, as well as an assemblage of other pico‐ and nanophytoplankton of mixed taxonomy. For each of these groups, dramatic variations in cell concentration were observed within the sampling period. Diel variations in cell scattering, which are indicative of changes in cell size, were consistent with patterns of cell growth during the light period and cell division late in the day. We developed a size‐structured matrix population model that accommodates simultaneous growth and division and then used the model and size distribution data from FlowCytobot to estimate daily specific growth rates for Synechococcus ; these estimates are independent of cell concentration and do not include mortality. The results show that a dramatic autumn decline in the concentration of Synechococcus can be attributed to a decrease in the specific growth rate rather than to effects of physical transport processes or trophic interactions.

Mixing Ratios and Photostationary State of NO and NO2 Observed During the POPCORN Field Campaign at a Rural Site in Germany - F. Rohrer; D. Brüning; E. S. Grobler; M. Weber; D. H. Ehhalt; R. Neubert; W. Schüßler; I. Levin (Journal of Atmospheric Chemistry, 1998)

Partition Behaviour of Drugs in Microemulsions Measured by Electrokinetic Chromatography - Y. Mrestani; R. H. H. Neubert; A. Krause (Pharmaceutical Research, 1998)

Direct Determination of Drug Content in Semisolid Formulations Using Step-Scan FT-IR Photoacoustic Spectroscopy - R. Neubert; B. Collin; S. Wartewig (Pharmaceutical Research, 1997)

Ofloxacin in juvenile non-human primates and rats. Arthropathia and drug plasma concentrations - R. Stahlmann; H. J. Merker; N. Hinz; I. Chahoud; J. Webb; W. Heger; D. Neubert (Archives of Toxicology, 1990)

LD50 versus acute toxicity - R. Baß; P. Günzel; D. Henschler; J. König; D. Lorke; D. Neubert; E. Schütz; D. Schuppan; G. Zbinden (Archives of Toxicology, 1982)